The Pay-Twice Critique, Government Funding, and Reasonable Pricing Clauses: Georgia State University, College of Law Journal of Legal Medicine Symposium. Issue 2 (3rd April 2019) - Wolitz, Rebecca E.
Abstract: The federal government subsidizes the research and development of prescription medications. Thus, a captivating critique of expensive medications is that prices are too high because of taxpayer co-financing. This critique is often framed in terms of "paying-twice"—first for the research and second through the above market pricing of resulting products. Reasonable pricing clauses—which place some kind of pricing limitation on the exercise of license or patent rights governing a federally funded medication—are one proposed policy tool for addressing the pay-twice critique. This article provides increased analytical clarity as well as historical context to present-day debates about the privatization of federally funded research and prescription drug pricing. It makes three arguments. First, despite its pervasiveness and intuitive plausibility, the pay-twice critique is subject to differing interpretations which has important implications for the appropriateness of proposed solutions. Second, despite their initial attractiveness, the costs, necessity, and effectiveness of reasonable pricing clauses render the wisdom of this policy tool uncertain. However, third, given continued interest in reasonable pricing clauses, the NIH's previous experience with such a policy offers some useful lessons.